Sepsis and Pediatric Acute Respiratory Distress Syndrome - Yehya, Nadir; Thomas, Neal J. (Journal of Pediatric Intensive Care, 2019)
The epidemiology of the acute respiratory distress syndrome (ARDS) in pediatric sepsis is poorly defined. With significant data extrapolated from adult studies in sepsis and ARDS, sometimes with uncertain applicability, better pediatric-specific guidelines and dedicated investigations are warranted. The recent publication of a consensus definition for pediatric ARDS (PARDS) is the first step in addressing this knowledge gap. The aim of this review is to frame our current understanding of PARDS as it relates to pediatric sepsis, encompassing epidemiology, pathophysiology, and management. We argue that addressing the role of PARDS in pediatric sepsis requires significant attention to details with respect to how PARDS and sepsis are defined to accurately describe their epidemiology, natural history, and outcomes. Finally, we highlight certain aspects of PARDS management as they relate to the septic child and offer suggestion for future directions in this field.
Keywords: sepsis; septic shock; children; pediatric; acute respiratory distress syndrome; pediatric acute respiratory distress syndrome